The role of the State Security Service (Stasi) in the context of international clinical trials conducted by western pharmaceutical companies in Eastern Germany (1961-1990) - Erices, Rainer; Frewer, Andreas; Gumz, Antje (PLoS ONE, 2018)
Background After the building of the Berlin Wall in the 1960s, a number of international pharmaceutical manufacturers from the West had their drugs tested in Eastern Germany (GDR). So far, the extensive collection of documents on the subject stored in the archives of the GDR State Security Service (Stasi, MfS) has not been systematically analysed. Until now, the role of the Stasi with respect to the surveillance of the trials has been unclear. Methods A keyword search within the database of the Stasi files was conducted. All available files were screened in order to identify institutions, companies and personnel involved in the clinical trials. On this basis, further files were requested. A total of 259 files were available for analysis. Relevant data was derived from 160 of these files. A contextualised approach was applied, which critically explored the origin, content, and impact of the data. In addition, an approach guided by the central steps of document analysis was applied. Results At least 400 clinical trials were conducted during the GDR period. The exact number remains speculative. According to references found in the Stasi files, it might have been considerably higher. Initially, the main goal of the trials was for the GDR authorities to decide whether to import certain Western drugs. By 1983, this intention had changed. Now, the primary aim of the trials was the procurement of foreign currency. The Stasi feared that the pharmaceutical companies could have a significant influence on GDR Health System. Stasi spies were holding positions in the responsible medical committees, universities, and hospitals. Constant surveillance by the Stasi served the purpose of monitoring any contact between people from the West and the East. Unknowingly, representatives of Western companies were surveilled by the Stasi. The studied documents also point to the fact that a number of clinical trials conducted during the GDR period did not comply with GDR regulations, and were therefore deemed illegal by the Stasi. The Stasi was not particularly interested in medico-ethical questions. Conclusions Clinical trials conducted during the GDR period were surveilled by the Stasi. It was their aim to monitor all people involved in the trials, including their Western contacts. Relevant medico- ethical questions like patient consent and safety with respect to the clinical trials were not the focus. Considering the significant number of conducted trials, only limited evidence exists of doctors having discussed them critically. The public was not officially informed about the trials.
CRIS-Team Scopus Importer:2023-03-21